How do state-owned and private-owned CVC differ in nurturing innovation in China? - Xiang Gao; Guoping Shi; Yige Wu; Luming Zhang (Journal of Risk and Financial Management, 2023)
We investigate how state-owned corporate venture capital differs from privately owned corporate venture capital in fostering innovation among startups. Based on the data of Chinese A-share listed companies and the startups in their portfolios that they invested in between 2009 and 2018, we find that startups backed by state-owned corporate venture capital are less innovative than startups backed by privately owned corporate venture capital. Using a two-stage least-squares analysis yields the same results. Further, we find evidence consistent with two potential mechanisms: Investors of state-owned corporate venture capital provide weaker technical support and are less tolerant of failure. These results have important implications for stakeholders, management, and policy makers who care about incentivizing young and rapidly growing companies to innovate more effectively.
Keywords: 650; China; firm innovation; privately owned corporate venture capital; startups; state-owned corporate venture capital